Chitosan-based bionanocomposites: Synthesis, properties, and applications - Azmana, Motia; Syed Mahmood, .; Nayeem, Abdullah; Mohd Azmir, Arifin (Elsevier B.V., 2023)
The complete dependency on synthetic and artificial materials threatens human life because they adversely affect our ecological system and affect the environment destructively. To mitigate that currently, the most talkative issue is to protect the environment by using biodegradable, nontoxic, biocompatible, and reusable materials for therapeutic, agricultural, food product manufacturing, and packaging purposes. In this case, chitosan-based materials show hopes, as chitosan is the second most plentiful natural biopolymer existing on the planet earth. Moreover, chitosan possesses film-forming abilities, antibacterial behavior, excellent mechanical and thermal properties. At present, chitosan-based bionanocomposite have appeared as ideal candidates for wide-ranging applications owing to the availability for surface modification together with their biodegradable, biocompatible, and nontoxic properties. However, this chapter highlights multiple aspects of chitosan such as its source, structural chemistry, properties, and modification. Additionally, It concentrates on chitosan-based bionanocomposites by describing its preparation techniques, characteristics, and applications. Finally, this chapter discusses the advantages and downsides of chitosan-based bionanocomposite to ensure its application superiority in numerous fields compared to other composites.